The Bacterial Quality of Lake Waters at Yellowknife, Northwest Territories - Bell, J.B.; Zaal, J.F.J.; Vanderpost, J.M. (ARCTIC, 1976)
A study was conducted to measure the degree of contamination of lake waters at Yellowknife produced by the disposal of domestic wastes, and to assess the suitability of these waters for domestic use. None of the samples analyzed met Canadian standards for drinking water. Though the bacterial quality of the main body of water was found to be good, there was contamination at points of discharge of sewage and near storm drains, marsh muds and sediments. It is recommended that the City of Yellowknife seek an alternative site for sewage disposal and give adequate publicity to the dangers of using inadequately treated water.